IMPLEMENTATION OF THE ONLINE SINGLE SUBMISSION (OSS) POLICY ON BUSINESS LICENSING SERVICES AT THE ONE-STOP INTEGRATED SERVICE INVESTMENT OFFICE (DPMPTSP) OF SINJAI REGENCY - Agus, Rezky Amelia; Aslinda, Andi; Guntur, Muhammad (Jurnal Aktor, 2025)
This study aims to determine the Implementation of the Online Single Submission (OSS) Policy on Business Licensing Services at the Sinjai Regency Investment and One-Stop Integrated Service (DPMPSTP) Office. This type of research is descriptive qualitative research with data collection techniques, namely interviews, observation, and documentation. Data analysis techniques use data condensation methods, data presentation, and conclusion drawing. The results of the study showed that the Implementation of the Online Single Submission (OSS) Policy on Business Licensing Services at the Sinjai Regency Investment and One-Stop Integrated Service (DPMPSTP) Office has been carried out well. This can be seen from the theory of George Edward III which is used to describe and explain the Implementation of the the Online Single Submission (OSS) in terms of four indicators, namely communication, resources, disposition, and bureaucratic structure.